Assessment of physical fitness among non-athlete adolescents: Effect of familiarization sessions - DIOGO HENRIQUE CONSTANTINO COLEDAM; RODRIGO DIAS CARIA DE OLIVEIRA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: ‪The validity and reliability of fitness tests are described in the literature; however, the effects of familiarization sessions on motor performance have not yet been studied. The aim of this study was to analyze the effects of four familiarization sessions on physical fitness performance among adolescents. Material and methods: ‪Twenty adolescents performed sprint, agility, flexibility, explosive strength, muscular endurance, and balance tests on four separate days with an interval of 72h. Results: ‪Considering the first and the fourth sessions, there were significant differences in mean values for push-up, curl-up, and Flamingo tests (p<0.05). Intraclass Correlation Coefficient (ICC) varied from 0.65 to 0.97, except for the Flamingo test (0.22). The magnitude based inference revealed a likely beneficial effect of familiarization on agility (87.8%), push-ups (91.2%), curl-ups (94.4%), and a very likely effect on the Flamingo test (97.0%). When comparing the second and the third sessions with the first one, values of ICC were similar or higher, while a likely beneficial effect of familiarization was found in the second session for the Flamingo test (78.8%), and in the third session for curl-ups (91.3%), push-ups (77.1%), and the Flamingo test (94.8%). Conclusions: ‪The familiarization procedure should be considered prior to agility, muscular endurance, and balance test assessments.